A checklist approach to evaluate the contribution of organic farms to landscape quality - Kuiper, Juliëtte (Agriculture, Ecosystems & Environment, 2000)
Criteria need to be developed to evaluate the cultural environment of European rural landscapes. The goal is to evaluate and encourage the contribution of organic farming to sustainable landscape quality. Two sets of criteria were used to evaluate the quality of the cultural environment, non-expert and expert values. The non-expert values consisted of criteria for the appreciation of the present local landscape by users and inhabitants. These criteria were derived from psychological principles (Coeterier, 1996). The expert values for landscape assessment were derived from physiognomy, geography and landscape architecture. These criteria require specialized knowledge essential in understanding the cultural history of at least the regional landscape and in landscape planning. The criteria were derived from a reﬂection of landscape plans at different scale levels (Kuiper, 1998). This reﬂection resulted in planning objectives based on the following three criteria: diversity; coherence; and continuity. Diversity refers to the diversity of landscape components as an expression of the relationships between land use and abiotic features; coherence refers to coherence among landscape components as an expression of the relationships between sites (hydrology, ecology and infrastructure); continuity refers to temporal relationships of land use and spatial arrangement from the past to the future. These three criteria are interrelated and inseparable. The need for ecological quality as well as aesthetic quality within the rural landscape is seen as a step forward in cultural development. To make EU regulations based on planning objectives seems premature at present. A checklist was established based on the criteria mentioned and was formulated in such a way as to compare an organic farm with a conventional farm in the same landscape unit. The checklist was implemented on organic and adjacent conventional farms in nine regions of Europe. In this article a large farm was considered in the Dehesa landscape in Andalusia and small farms were considered in the fringe of Lisboa, in the Netherlands and on Crete. The two sets of criteria proved able to include all the arguments named during the evaluation of the contribution of organic farms to landscape quality
Keywords: diversity and coherence; landscape quality; organic farms